PAMERAN VIRTUAL SEBAGAI SALAH SATU UPAYA PROGRAM PENJANGKAUAN KEARSIPAN OLEH ARSIP UNIVERSITAS GADJAH MADA: Array - Herman Setyawan (Arsip Nasional Republik Indonesia, 2020)
Archives have a broad role for organizations. That is why it needs to be published. Archive publication is an effort to reach the public. Virtual exhibitions is one of the outreach efforts that can be done during the current COVID-19 pandemic. The purpose of this study was to analyze one of the archival outreach programs at the Gadjah Mada University Archives. Some things that are analyzed are the process of virtual exhibition activities, contents, and the factors that influence the visit to the official UGM Archives page. Through a case study approach, this study seeks to describe some things analyzed. The results showed that the virtual exhibition process was carried out systematically and continuously, content coverage is quite diverse, and the factors that influence a visit to the official UGM Archives page can be identified.